Brake blending and torque vectoring of road electric vehicles: a flexible approach based on smart torque allocation. (1st March 2020) - Pugi, Luca; Favilli, Tommaso; Berzi, Lorenzo; Locorotondo, Edoardo; Pierini, Marco
Application of regenerative braking on electric vehicles has a large impact on several aspects of design, implemented functionalities and overall performances of road vehicles. In particular, multi-quadrant capabilities and improved control performances of modern electric drives can be fully exploited to improve vehicle efficiency, stability and overall environmental impact. Conventional, mechanical friction brakes are currently devoted not only to stop the vehicle but also to the actuation of safety related mechatronics systems such as electronic braking distribution (EBD), AntiBlockierSystem (ABS) and electronic stability control/program (ESC/ESP). The result is an over-actuated system of electrical (electric motors) and mechanical actuators (friction brakes), whose mixed, blended application has to be carefully optimised. In this work a simplified approach is proposed in which concepts transferred from previous studies on high speed trains and autonomous vehicles are re-purposed and adapted in an innovative way to electric road vehicles.